Evaluasi Berat Badan Dengan Tingkat Penerapan Good Farming Practice Pada Peternakan Sapi Potong di Kabupaten Bone : Evaluation of Body Weight Based on the Implementation of Good Farming Practices in Cattle Farming of Bone Regency - Yunus, Muhammad; Azhar, Muhammad; Sara, Urfiana (Fakultas Peternakan Universitas Jambi, 2026)
Background: Increasing beef production is influenced not only by the growth of the cattle population but also by the achievement of optimal body weight performance. The application of appropriate husbandry standards is essential to ensure effective management and the production of high-quality meat. Good Farming Practices (GFP) serve as a key approach to improving productivity in beef cattle systems. Purpose: This study aimed to evaluate the level of GFP implementation among beef cattle farmers, analyze the relationship between GFP scores and estimated body weight, and determine the contribution of GFP-based management factors to production performance in Bone Regency. Method: The study was conducted in Barebbo District involving actively operating beef cattle farmers as respondents. Independent variables included housing (X1), feeder cattle selection (X2), feeding (X3), and animal health and welfare (X4). The dependent variable was the estimated body weight of beef cattle (Y). Data were collected through structured interviews and body weight estimation measurements. Data analysis included GFP performance assessment, correlation analysis to assess relationships among variables, and multiple linear regression to quantify the contribution of each management factor to body weight. Results: GFP implementation varied across management aspects, with feeding achieving the highest score. Feeding management and animal health and welfare exerted the strongest influence on body weight improvement, followed by feeder cattle selection, while housing showed no meaningful effect. These findings emphasize the critical role of nutrition management, animal health care, and environmental comfort in enhancing growth and productivity. Conclusion: The high coefficient of determination indicates that consistent GFP implementation positively affects production performance. Strengthening standardized husbandry practices is recommended as a strategic effort to support the development of beef cattle farming in Bone Regency.